Modelling biome shifts and tree cover change for 2050 in West Africa - Heubes J; Kühn, I.; König, K.; Wittig R; Zizka G; Hahn K (Wiley, 2011)
Africa is expected to face severe changes in climatic conditions. Our objectives are: (1) to model trends and the extent of future biome shifts that may occur by 2050, (2) to model a trend in tree cover change, while accounting for human impact, and (3) to evaluate uncertainty in future climate projections.